Combined drought and bark beetle attacks deplete non‐structural carbohydrates and promote death of mature pine trees. (20th October 2021) - Erbilgin, Nadir; Zanganeh, Leila; Klutsch, Jennifer G.; Chen, Shih‐hsuan; Zhao, Shiyang; Ishangulyyeva, Guncha; Burr, Stephen J.; Gaylord, Monica; Hofstetter, Richard; Keefover‐Ring, Ken; Raffa, Kenneth F.; Kolb, Thomas
Abstract: How carbohydrate reserves in conifers respond to drought and bark beetle attacks are poorly understood. We investigated changes in carbohydrate reserves and carbon‐dependent diterpene defences in ponderosa pine trees that were experimentally subjected to two levels of drought stress (via root trenching) and two types of biotic challenge treatments (pheromone‐induced bark beetle attacks or inoculations with crushed beetles that include beetle‐associated fungi) for two consecutive years. Our results showed that trenching did not influence carbohydrates, whereas both biotic challenges reduced amounts of starch and sugars of trees. However, only the combined trenched‐bark beetle attacked trees depleted carbohydrates and died during the first year of attacks. While live trees contained higher carbohydrates than dying trees, amounts of constitutive and induced diterpenes produced did not vary between live and beetle‐attacked dying trees, respectively. Based on these results we propose that reallocation of carbohydrates to diterpenes during the early stages of beetle attacks is limited in drought‐stricken trees, and that the combination of biotic and abiotic stress leads to tree death. The process of tree death is subsequently aggravated by beetle girdling of phloem, occlusion of vascular tissue by bark beetle‐vectored fungi, and potential exploitation of host carbohydrates by bark beetle symbionts as nutrients. Abstract : Colonization of drought‐stressed trees by bark beetles and their associated microbes reduced local carbohydrate availability for essential tree functions and also inhibited tree's ability to replenish carbohydrate reserves. Furthermore, production of terpenes and spreading fungal biomass in tree tissues became sinks for carbohydrates, leading to tree death.